Heaven : our enduring fascination with the afterlife - Miller, Lisa. (New York : Harper, 2010)
A groundbreaking and accessible history of heaven--from the earliest biblical conceptions of the afterlife to the theologians who frame our understandings, to the convictions and perceptions of everyday people. Drawing on history and popular culture, biblical research and everyday beliefs, religion journalist Lisa Miller offers a new understanding of one of the most cherished ideals of spiritual life. She discusses not just our visions of the afterlife, but how our beliefs have influenced the societies we have built and the lifestyles to which we have subscribed. She also reveals how the notion of heaven has been used for manipulation--to promulgate goodness and evil--as inspiration for selfless behavior, and as justification for mass murder. From the Revelation to the Left Behind series, Augustine to bin Laden, Muslims in the West Bank to American Mormons baptizing their dead, this is a penetrating look at a cherished religious ideal.--From publisher description.
What is heaven? -- The miracle -- The kingdom is near -- Green, green pastures -- Resurrection -- Salvation -- Visionaries -- Reunions -- Is heaven boring?
Includes bibliographical references (p. [255]-320) and index.
College Student
Keywords: Heaven; Abrahamic religions; Heaven -- Christianity; United States -- Religion